PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV B SDN 004 TERATAK BULUH KABUPATEN KAMPAR - Hendra Wati; Gustimal Witri; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The process of learning that teachers centered learning, while students just shut up and accept what is. This makes it less active and creative students in the learning process so as to make student learning outcomes is low. Therefore, in order that the student learning outcomes better, the researchers interested in conducting research aimed at improving student learning outcomes IPS. This research applies problem-based learning model, which is implemented in the fourth grade B 004 Teratak Buluh Elementary School. The results of this study are: Activities of teachers, teacher activities undertaken at the first meeting by 60%, then 65% in the second meeting, the third meeting increased to 80%, then the fourth meeting increased again by 85%. Student activities, student activities undertaken at the first meeting by 60%, then 70% in the second meeting, the third meeting increased to 75%, then the fourth meeting increased again by 85%. The results of study, Application of Problem Based Learning Model to improve learning outcomes IPS fourth grade students of SD Negeri 004 Teratak Buluh this can be seen from the results of students' average initial data 71.79, 74.75 and UH-I of UH-II 81.00 , from initial data to the UH-I increased 2.96 (4.12%) and of the initial data to the UH-II rise again as much as 9.21 (12.83%). In the learning outcomes in the classical completeness reached 85% and classically can be said to be complete. It can be concluded that the Application of Problem Based Learning Model to improve learning outcomes IPS Elementary School fourth grade SDN 004 Teratak Buluh. Keywords: Model Problem Based Learning, Learning IPS SD, learning outcomes